Cysticercus cellulosae Regulates T-Cell Responses and Interacts With the Host Immune System by Excreting and Secreting Antigens - Fan, Xianmin; Zhang, Yue; Ouyang, Renhui; Luo, Bo; Li, Lizhu; He, Wei; Liu, Meichen; Jiang, Nan; Yang, Fengjiao; Wang, Lingjun; Zhou, Biying (Frontiers in Cellular and Infection Microbiology, 2021)
It is unclear whether the immune response and cytokine production caused by cysticercus cellulosae infection are related to the regulation of immune response by cysticercus cellulosae excretion and secretion antigens during the parasitic process. In this regard, the purpose of this study used cysticercus cellulosae crude antigens (CA) as a control, the aim of it was to explore the effect of ESA on T cell immune response of piglets. We demonstrated cysticercus cellulosae excretory secretory antigens (ESA) to induce imbalance of CD4+/CD8+ T cells proportion. ESA was further capable of increasing the frequencies of CD4+Foxp3+ and CD8+Foxp3+ T cells, as well as inducing the production of IL-10 in lymphocytes, which was mainly attributed to CD4+ and CD4-CD8- T cells. Moreover, it can also induce the production of Th2 type immune response. The results showed that the immune escape of cysticercus cellulosae and the establishment of persistent infection may be related to the regulation of host immune response by ESA.